Asterix and the magic carpet - Uderzo (Asterix adventure, 2002)
This is the 30th book in the popular Asterix series, in which Asterix travels on a magic carpet to India. The wonderful village where Asterix and Obelix live has only one drawback: its bard is the worst musician in the ancient world. Whenever Cacofonix strikes up a tune, the sun hides behind the clouds and the rain begins to fall. But, then a fakir flies in on a magic carpet asking for help in ending a terrible drought in his kingdom. Otherwise, his daughter Orinjade will be sacrificed to the gods. Suddenly, Cacofonix's talents come in mighty handy.